Ethnic Federalism and Social Cohesion in Ethiopia - Gebiso, Meseret Tesfaye (University of the Witwatersrand, Johannesburg, 2023)
As an ethnically diverse country of more than eighty ethnic groups, Ethiopia adopted ethnic-federalism system in 1995. Ever since its adoption, the system has been a very controversial subject in Ethiopia. The discourse on the issue has been very polarised. This study explores the relationship between the ethnic federalism system and social cohesion in Ethiopia so as to contribute to the discourse with empirical evidence and analysis which is lacking in the Ethiopian context. Primary narrative data that is interviews of key informants and secondary data from international data bases is employed to answer the research question. The secondary data analysis has illustrated that conflicts and violence have significantly increased and social cohesion is declining. The primary data analysis has revealed that the system’s narratives, structures and implementations strengthened exclusive identities; incentivised elite behaviours that lead to conflicts and violence. Overall, the findings indicated that the ethnic federalism system has played a role in the erosion of inter- ethnic cohesion and in increasing inter-ethnic conflicts and violence
A research report submitted in partial fulfillment of the requirements for the degree of Master of Master of Management (in the field of Public Policy) to the School of Governance, Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, 2023
Keywords: Ethopia; Ethnic federalism; Social cohesion; Inter-ethnic conflicts; UCTD; SDG-11: Sustainable cities and communities